Analisis Pengetahuan Ibu Tentang Tumbuh Kembang Dengan Perkembangan Motorik Kasar Usia 1-2 Tahun Di Wilayah Kerja Puskesmas Parsoburan Kota Pematang Siantar Tahun 2023 - Magdalena Junita Sumiati Tambunan; Martaulina Sinaga; Sri Mulati Nendah Agreta; Rosmega Rosmega; Cici Framita Lbn Gaol; Aprialdo Pranata Sidauruk (Jurnal Anestesi, 2023)
Delayed motor development in children means that motor development has not been developed as it should be, at the child's age, which results in the child not being able to carry out developmental tasks appropriate to his age group. Delayed motor development in children, some of which can be controlled and some of which cannot. This delay is often caused by the child's lack of opportunity to learn motor skills, excessive parental protection, or the child's lack of motivation to learn them. This research was carried out at the Parsoburan Community Health Center, Siantar Marihat District, Pematang Siantar City with a sample size of 53 respondents. After conducting research on the relationship between mothers' knowledge about the growth and development of toddlers and gross motor development aged 1-2 years in the work area of ??the Parsoburan Health Center, Siantar Marihat District, Pematang Siantar City in 2023, it can be concluded that there is a relationship between mothers' knowledge about the growth and development of toddlers and gross motor development at age. 1-2 Years in the Working Area of ??the Parsoburan Health Center, Siantar Marihat District, Pematang Siantar City in 2023